Examining the Dimensions of the Character of Abji Khanum in the Short Story of Sadegh Hedayat and Miss Kilman in the Novel "Mrs. Dalloway" by Virginia Woolf - Hossein Taheri (ادبیات تطبیقی, 2023)
Introduction  Mrs. Dalloway’s novel is the story of a fine day in London in 1923; Clarissa Dalloway is preparing a big party and many people are introduced during her tours of the house, the town and her relationships with others. She has hired a tutor for her daughter Elizabeth, whose name is Miss Doris Kilman. She is one of the non-main characters who has a short presence, But it is very strong in the novel. While promoting the party and in just a few pages, the author shows us Kilman’s character from the mind and point of view of  Clarissa, Elizabeth and Kilman herself and the author reveals her appearance and psyche. In Hedayat's short story, Abji is an ugly girl who, although she is twenty-two years old, her time for marriage has passed and because she has no hope of any enjoyment in this world, she has taken refuge in religion and hopes for the blessings of the other world in heaven. She commits suicide in her younger sister's wedding due to humiliation and jealousy. Hedayat wants to show the destructive effects of people's beliefs. Therefore, the tragic end of Abji khanum's story is a bitter criticism of the culture of his time. 2.MethodologyToday, intertextuality has provided the necessity of research between texts; the discussion of texts and intertextual influences examines the many commonalities and differences in the texts. This issue is the main necessity of all comparative research. This article, with the library method and characterological investigation of two stories that have different origins, habitats and languages, seeks to compare many similarities and differences of these two stories characters. 3.DiscussionEach person's unique personality is made from his genetics, environment, interaction and lived experience with others; But some factors cause the emergence of similar characters, If one person interprets an experience as similar to another person, then their processes are psychologically similar. This is how the characters analyzed in this article, namely Abjikhanam and Doris Kilman, are similar. Abjikhanam and Doris Kilman, although they were created in two different countries, cultures, times and languages, have deep similarities to each other; Because they have similar psychological, interpersonal and family background. Wolff's view of the female characters in his stories is combined with feminist attention. There are many women in Mrs. Dalloway, each of them is treated as necessary; But in the characterization of Doris Kilman, she used a lot of precision and in addition to characterization techniques, she also used psychoanalysis. Hedayat also considered the psychological dimensions and invisible causes of behavior in dealing with Abji's character, and both works have a psychological infrastructure. The influence of family, community and relationships in the formation of human characters is undeniable; The basis of the personality of both women in both works is in addition to the direct psychological aspects related to the family and the dominant culture of the time. 4.ConclusionIn the comparative analysis of the characters of Doris Kilman and Abji Khanum, it should be noted that both authors have spoken about the past of the characters in such a way that their current personality, intellectual and psychological characteristics can be seen. Also, the influence of family and general culture is prominent in the formation of both stories; Poverty and ugliness have increased Doris Kilman's sense of humiliation. She is alone, she has no supporter, friend or family, and most importantly, she has never been able to attract a man's attention. She is looking for a replacement to fill all her emotional and psychological voids; So she goes to church. Now she is a radical Christian. Abji khanum is also the same; she is ugly, she has a poor and ignorant family, she grew up with humiliation and discrimination from childhood, and as a result, she is now grumpy, jealous, hopeless and self-deprecating; her compensatory behavior is the extreme refuge in the mosque. Both characters believe that they should win over everyone and show off their superiority; Abji wants to achieve this goal with religious knowledge and Doris with her university degree. In addition, both of them wish for a situation where the differences between people disappear and everyone is equal; A condition or situation like heaven.The misbehavior and aggression of these two are also reactions of two damaged and wounded souls, with the difference that Doris had a happy life in Germany as a child; But Abji khanum has not benefited from this blessing either. Her mother always beat her and told her from the age of five that she was ugly and no man would marry her. The suicide of Hedayat's character shows the difference between his attitude and Wolff's. Woolf was an egalitarian feminist and wrote the character of Doris in such a way as to show her stubbornness in the unequal male system: Doris struggles for her life. Woolf - contrary to Hedayat - lived in a time when women had taken great strides for their rights. So, these two oldgirls have two different destinies, because the historical-cultural conditions and environmental conditions and the views of their authors are different.